Accessing Expert‐Curated Pharmacological Data in the IUPHAR/BPS Guide to PHARMACOLOGY. Issue 1 (9th April 2018) - Sharman, Joanna L.; Harding, Simon D.; Southan, Christopher; Faccenda, Elena; Pawson, Adam J.; Davies, Jamie A.; ,
Abstract: The IUPHAR/BPS Guide to PHARMACOLOGY is an expert‐curated, open‐access database of information on drug targets and the substances that act on them. This unit describes the procedures for searching and downloading ligand‐target binding data and for finding detailed annotations and the most relevant literature. The database includes concise overviews of the properties of 1, 700 data‐supported human drug targets and related proteins, divided into families, and 9, 000 small molecule and peptide experimental ligands and approved drugs that bind to those targets. More detailed descriptions of pharmacology, function, and pathophysiology are provided for a subset of important targets. The information is reviewed regularly by expert subcommittees of the IUPHAR Committee on Receptor Nomenclature and Drug Classification. A new immunopharmacology portal has recently been added, drawing together data on immunological targets, ligands, cell types, processes and diseases. The data are available for download and can be accessed computationally via Web services. © 2018 by John Wiley & Sons, Inc.